Repression, resistance, and women in Afghanistan - Emadi, Hafizullah (Praeger, 2002)
Afghan women have faced an exhaustive struggle in the battle to change their status and improve their situation. Emadi takes a long look at the role of development and modernization policies implemented by the state in the pre- and post-Soviet eras, under the Taliban, and beyond. He finds that such policies have failed to bring about much- needed change and improvement for women. Modernization strategies benefited only a small segment of urban women and left the plight of rural women unchanged. Although a small segment of middle- and upper-class women organized themselves and fought to bring about changes in their status and to end gender inequality, their efforts alone did not meet with much success.